THE INFLUENCE OF CONSUMER PERCEPTION AND BRAND AWARENESS ON THE INCREASE OF ONLINE SALES OF AEROSTREET PRODUCTS ON THE TIKTOK SHOP PLATFORM - Muhammad Hafizh Ridho; Ety Dwi Susanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of digital technology has driven significant changes in marketing strategies and consumer behavior. TikTok Shop has emerged as a social commerce platform that combines entertainment with shopping activities through short video content and real-time interactions. Aerostreet, a local shoe brand, utilizes this platform to expand its market reach and increase its competitiveness. However, sales growth is not solely determined by digital marketing activities, but also by consumer perception and brand awareness. Based on this phenomenon, this study formulates three main questions: whether consumer perception and brand awareness simultaneously have a significant effect on increasing online sales, whether consumer perception has a significant partial effect, and whether brand awareness partially contributes to increasing Aerostreet product sales on TikTok Shop. This study aims to analyze the influence of consumer perception and brand awareness using a quantitative associative approach through multiple linear regression. Data were obtained from 100 respondents, TikTok Shop users who purchased Aerostreet products. The results show that both independent variables simultaneously have a significant effect on increasing online sales. Partially, consumer perception and brand awareness both have a significant positive effect. The coefficient of determination (R²) indicates a fairly strong contribution of both variables to increasing online sales. This study emphasizes the importance of building positive perceptions and increasing brand awareness in supporting the success of digital marketing in the era of social commerce.